International Networks and Their Potential Contribution to Crop and Soil Management Research - Greenland, D. J.; Craswell, E. T.; Dagg, Matthew (SAGE Publications, 1987)
Agricultural research networks are playing a key role in the coordination of international efforts to develop improved technologies for food production by farmers in developing countries. This paper reviews the role of these networks in making possible the evaluation, adaptation, and extrapolation of crop and soil management studies, and so improving the efficiency of much agronomic and soil research. The advantages which may be gained by national agricultural systems from participation in international networks are described, as well as problems.